2004
DOI: 10.2466/pr0.94.2.562-564
|View full text |Cite
|
Sign up to set email alerts
|

Three Stress Groups on Their Stressors and Reactions to Stressors in Five Studies

Abstract: A comparison of means and SDs for responses from three stress groups on the Student-life Stress Inventory in five studies over 13 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 1 publication
1
10
0
6
Order By: Relevance
“…SLSI was designed by Gadzella [ 24 ]. SLSI has 51 items with five stress categories (frustration, conflicts, pressures, changes, and self-imposed) and four categories of reactions to stressors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SLSI was designed by Gadzella [ 24 ]. SLSI has 51 items with five stress categories (frustration, conflicts, pressures, changes, and self-imposed) and four categories of reactions to stressors.…”
Section: Methodsmentioning
confidence: 99%
“…Each item uses a 5-point scale; the total score is the sum of the nine categories. The purpose of the SLSI was to assess the mean responses to different stressors and reactions to stressors among students [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The independent variable was personal and academic stress level, which was measured by the Student-life Stress Inventory (SSI) (see Appendices E and F) (Gadzella, 1991). The self-report paper and pencil instrument, developed from a theoretical model described by Morris (1990) The Student-life Stress Inventory (SSI) has been used in numerous studies to measure college student stress and to determine the reliability and validity of the instrument (Gadzella, 1991(Gadzella, , 1994a(Gadzella, , 1994b(Gadzella, , 2004Gadzella & Baloglu, 2001;Gadzella & Carvalho, 2006;Gadzella, Fullwood, & Ginther, 1991;Gadzella, Fullwood, & Tomcala, 1992;Gadzella, Masten, & Stacks, 1998). For example, concurrent validities were reported for the SSI for 95 students in 1991 (Cronbach's alpha ranging from .52 for the Frustrations scale to .85 for the Changes scale), 290 students in 1994 (p = .0009), and 381 male and female students enrolled in psychology courses at all levels of a state university in 2001 (Cronbach's alpha = .92) (Gadzella, 1994b;Gadzella & Baloglu, 2001;Gadzella, Fullwood, et al, 1991).…”
Section: Instrumentationmentioning
confidence: 99%
“…In another study, internal consistency coefficients for each of the nine sections of the SSI and the total inventory values were computed for 95 students on three-week testretest responses, and ranged from .57 (cognitive) to .76 (emotional) (Gadzella, Fullwood, et al, 1991). In addition, when a comparison of means and standard deviations for responses from three stress groups (mild, moderate, and severe) on the SSI were analyzed in five studies over 13 years, significant differences among the groups were found on all nine sections of the instrument (Gadzella, 2004). Students perceiving severe stress scored higher on both the stressor and reactions subscales than those students reporting moderate or mild stress levels (Gadzella, 2004).…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation